Indoor Patient Satisfaction on Doctor’s Care: A Tool to Improve Quality Service at Tertiary Level Military Hospital, Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Patient satisfaction Survey has become a regulatory Tool to ensure quality of services and efficient use of resources. To endure quality service In-patient departments, doctors’ care undoubtedly a useful measure in CMH (Combined Military Hospital) where the number of patient flow is increasing day-by-day.Objective: To find out the perceptions and expectations of the patients from the doctors in a tertiary level military hospital.Materials and Methods: In this descriptive cross sectional study 372 respondents were selected among the admitted patients of CMH Bogra. Respondents were randomly selected from all wards and were interviewed with a semi-structured questionnaire from May 2015 to December 2015.Results: Out of 372 respondents, 68.8% were in age group between 25 to 50 years and majority (69%) of them were army personnel. Overall patients’ highly satisfaction levels on doctor’s services were doctors’ attitude (66%), patients’ privacy maintenance (61%), regular Ward visit (70%), counselling (59%) and importance of patients’ opinion (62%). Requirement of increased number of doctors and initiation of professional development program (PDP) for physicians were found important.Conclusion: In Military Hospital, doctors are more accountable to their work. Therefore a management approach must be higher with more complicated expectation levels. This study showed a higher level of indoor patient satisfaction with doctors care at CMH Bogra.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 76-84